Institutional Readiness of Baubau City Regional General Hospital in Implementing the Standardised Inpatient Care Class Policy - Andi Yaumil Bay Ramdayana Thaifur; Reski Dewi Pratiwi; Mangindara Mangindara; Afriyana Amelia Nuryadin; Julia Bani (Direktorat Politeknik Kesehatan Makassar, 2026)
The Standardised Inpatient Care Class (KRIS) is a national policy within the National Health Insurance (JKN) programme in Indonesia that mandates hospitals to fulfil 12 technical criteria to ensure equitable inpatient services for all BPJS Kesehatan participants. This study evaluated the institutional readiness of Baubau City Regional General Hospital in implementing KRIS as mandated by Presidential Regulation (No.59/2024). A convergent mixed-methods design was employed, involving four key informants with direct authority over the implementation process. Data were collected through in-depth interviews, readiness assessments based on the 12 KRIS criteria, direct field observations, and document reviews. Qualitative and quantitative data were analysed separately and integrated during interpretation using SWOT and fishbone analyses. The findings indicated that the hospital had not yet achieved readiness to implement KRIS, particularly in infrastructure standards, clinical-support facilities, and service system requirements. Major barriers included limited regional fiscal capacity, disparities in governance authority between local and centrally managed hospitals, and weak inter-unit coordination. These constraints may affect policy implementation effectiveness and equitable service delivery. The study concludes that Baubau City Regional General Hospital remains institutionally unprepared for full KRIS implementation. A phased PDCA (Plan–Do–Check–Act) approach is recommended to strengthen infrastructure readiness, coordination mechanisms, and institutional implementation capacity.